2018
DOI: 10.1111/1750-3841.14401
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Bacterial, Viral, and Protozoan Pathogens in Field and Market Strawberries and Environment of Strawberry Farms

Abstract: Field-grown strawberries, the environment of strawberry farms and fresh strawberries from marketplaces were examined for bacterial, viral, and protozoan pathogens. The presence of bacteria was determined using culture and real-time PCR (qPCR), presence of protozoa and viruses using qPCR and reverse transcription qPCR, respectively. The highest proportion of positivity was observed for Escherichia coli both in field and purchased strawberries (up to 48.6%). Finding of Cronobacter ranged from 0.6% to 9% both for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…(2017) reported no L. monocytogenes in the fresh-cut strawberries studied. Similar results were found by Dziedzinska et al. (2018), where L. monocytogenes detection was reported as sporadic with only one positive sample from all field strawberries (0.6%) and one positive sample of purchased strawberries (1.4%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…(2017) reported no L. monocytogenes in the fresh-cut strawberries studied. Similar results were found by Dziedzinska et al. (2018), where L. monocytogenes detection was reported as sporadic with only one positive sample from all field strawberries (0.6%) and one positive sample of purchased strawberries (1.4%).…”
Section: Discussionsupporting
confidence: 87%
“…Blackberry was the only fruit found positive for E. coli which was detected in just two out of 75 berry samples. However, in another study a high proportion of positive samples was observed for E. coli both in field and purchased strawberries (up to 48.6%) but with counts less than 100 cfu g −1 (Dziedzinska et al., 2018). Levels of fecal organisms, such as E. coli are a better indicator of contamination (Nguyen-The and Carlin, 1994) and this could explain why this organism has been included as a hygienic criterion in the EU regulation (No 2073/2005) (Anonymous, 2005).…”
Section: Discussionmentioning
confidence: 92%
“…(2015) found generic E. coli on only 2 of 72 (2.8 %) of strawberry samples from primary production in Belgium, at concentrations of 1.0 log 10 CFU/g and 3.0 Log 10 CFU/g and Dziedzinska et al (2018) found 9.0 % (14 of 156) of strawberry field samples contaminated with E. coli in the Czech Republic, and 1.4% from marketplaces (1 of 70).…”
Section: Total Coliform Counts and E Colimentioning
confidence: 99%
“…The incidence of NoV in strawberry matrix can be explained because viral contamination can occur in all parts of food chain (Dziedzinska et al, 2018)…”
Section: Norovirus Gi and Giimentioning
confidence: 99%
“…Subsequently, 1200 mL of the mixture was applied to the spin column, and the manufacturer's protocol followed. Water samples were processed as previously described in Dziedzinska et al 37 Briefly, water samples (10 L) with pH lowered to 3.5 were passed through negatively charged filters (cellulose nitrate HA Millipore membrane, 0.45-mm pore size; Merck, Darmstadt, Germany). Elution of viral particles by beef extract solution (3% w/v; pH 9.5) in glycine buffer (0.05 mol/L) followed.…”
Section: Viruses Targeted and Origin Of The Samplesmentioning
confidence: 99%